Solar XUV and ENA‐driven water loss from early Venus' steam atmosphere. Issue 5 (14th May 2016) - Lichtenegger, H. I. M.; Kislyakova, K. G.; Odert, P.; Erkaev, N. V.; Lammer, H.; Gröller, H.; Johnstone, C. P.; Elkins‐Tanton, L.; Tu, L.; Güdel, M.; Holmström, M.
Abstract: We present a study on the influence of the upper atmosphere hydrodynamic escape of hydrogen, driven by the solar soft X‐ray and extreme ultraviolet radiation (XUV), on an expected outgassed steam atmosphere of early Venus. By assuming that the young Sun was either a weak or moderately active young G star, we estimated the water loss from a hydrogen dominated thermosphere due to the absorption of the solar XUV flux and the precipitation of solar wind produced energetic hydrogen atoms (ENAs). The production of ENAs and their interaction with the hydrodynamic extended upper atmosphere, including collision‐related feedback processes, have been calculated by means of Monte Carlo models. ENAs that collide in the upper atmosphere deposit their energy and heat the surrounding atmosphere mainly above the main XUV energy deposition layer. It is shown that precipitating ENAs modify the thermal structure of the upper atmosphere, but the enhancement of the thermal escape rates caused by these energetic hydrogen atoms is negligible. Our results also indicate that the majority of oxygen arising from dissociated H2 O molecules is left behind during the first 100 Myr. It is thus suggested that the main part of the remaining oxygen has been absorbed by crustal oxidation. Key Points: Hydrodynamic escape influences the atmospheric composition and evolution ENAs deposit their energy and heat the surrounding gas above the main XUV energy deposition layer ENAs modify the thermal structure of the atmosphere, but the enhancement of the escape is negligible